KEPEMIMPINAN DIGITAL KEPALA SEKOLAH DALAM MENGHADAPI TRANSFORMASI PENDIDIKAN KEJURUAN ERA SOCIETY 5.0: STUDI LITERATUR - Putri Panggabean; Nizwardi Jalinus; Ernawati Ernawati; Elfi Tasrif (STKIP Pesisir Selatan, 2026)
A school principal's digital leadership is a key factor in the transformation of vocational education. Unlike conventional leadership, digital leadership requires the ability to build a cohesive technology vision and manage a digital ecosystem. This study aims to identify the competencies, impacts, and challenges of digital leadership among vocational high school principals and to formulate a leadership model that aligns with the needs of vocational education in the Society 5.0 era. Methods: This study employed a Systematic Literature Review (SLR) using the PRISMA protocol. A total of 25 scientific articles published between 2020 and 2025 from various reputable databases were analyzed using thematic narrative synthesis. Results: Digital leadership has been shown to support technology integration in learning, pedagogical innovation, teacher collaboration, and school quality improvement. Key competencies include technological vision, data literacy, digital platform management, and change leadership. Major challenges include limited infrastructure, digital competency gaps, and resistance to change. Novelty: This study proposes the SATRIA Model (Strategic, Adaptive, Transformative, Responsive, Inclusive, and Accountable) as a digital leadership framework for vocational high school principals to support the transformation of vocational education in the Society 5.0 era.